1987
DOI: 10.2739/kurumemedj.34.183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological evaluation of early gastric cancer and lymph node metastasis.

Abstract: Four hundred fifty-nine solitary early gastric cancers were studied, retrospectively. There were 313 men and 146 women. The proportion for solitary early gastric cancer of the total gastric cancers was 23.4 % (459/1960). Early cancers were grossly divided into three fundamental types. One hundred nine cancers (23.7 %) were the elevated type, 8 cancers (1.7 %) were the flat type, and the depressed type was the most frequent, present in 342 of the patients (74.5 %). Early cancers were also divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The incidence of early gastric cancers has increased to about 50% of gastric cancers in Japan recently (Takeda et al 1987), as compared with about 10-15% in Europe (Borchard, 1990). However, the detection rate of early cardia cancer is still low, being only 11.7 % in our pre-sent study and 15.6% in a study by Okamura et al (1987).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of early gastric cancers has increased to about 50% of gastric cancers in Japan recently (Takeda et al 1987), as compared with about 10-15% in Europe (Borchard, 1990). However, the detection rate of early cardia cancer is still low, being only 11.7 % in our pre-sent study and 15.6% in a study by Okamura et al (1987).…”
Section: Discussionmentioning
confidence: 99%
“…R2-gastric resection which involves gastrectomy, omentectomy and the complete removal of Groups 1 and 2 regional lymph nodes has been gererally accepted as the procedure of choice for the treatment of EGC. As a result, surgical treatment for EGC patients has achieved an excellent 5 year survival rate of about 97% (Kitaoka et al 1984;Takeda et al 1987). Habu et al (1986) reported that cancer recurrences occurred more often in patients who had undergone no lymph node dissection (9.4%) than in those who had undergone lymph node dissection (1.5 Ā°o) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the lymph node metastasis rate in m -cancer was low, 3-5% has been reported (Fu jita et al 1983;Takeda et al 1987), and metastases were mainly observed in the Group 1 lymph nodes in a previous study (Takeda et al 1987).…”
Section: Introductionmentioning
confidence: 88%